ANALISIS BAHAYA BENCANA BANJIR BANDANG- DAN KERENTANAN FISIK DI NAGARI GUGUAK SARAI, KECAMATAN SUNGAI LASI, KABUPATEN SOLOK - Abdul Hadi Putra; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
Abstract The flash flood that occurred in November 2017 in Nagari Guguak Sarai, Sungai Lasi District, Solok Regency caused damage to settlements and agricultural land. The cause of flash flood is landslides in the upstream of the river due to high rainfall. To find out the areas that are potentially dangerous due to the flow of flash flood and the damage affected, it is necessary to map the flash flood hazard index using the mix method. As a result, the total area of ​​the flash flood hazard area reaches 373.347 ha and the area of ​​physical vulnerability reaches 12.33 ha with an estimated loss of more than 200 million rupiah for house damage and an estimated loss of more than 400 million rupiah for damage to public facilities. The flash flood hazard index map is used as a reference to determine areas that have the potential for flash flood overflows and the physical vulnerability map is used as a measurement of physical damage losses due to flash floods in Nagari Guguak Sarai. Keywords— Flash Flood Hazard, Hazard Index, Mix method, physical vulnerability